The Effect of Role Playing On The Social Ability of Children Aged 4-5 Years - Kustini, Kustini; Himmah, Faiqotul (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Early childhood education is one of the appropriate institutions to support child development. This type of research uses quasi experimental or quasi-experimental. The study population was 70 children consisting of Kindergarten A, Kindergarten B. The sampling technique used a Probability sampling technique, namely saturated samples or often referred to as total sampling, where the experimental class was taken randomly. The data collection instruments used observation guidelines, documentation and data analysis techniques using descriptive statistics and inferential statistics. The results of this study indicate a significant influence between role playing methods and children's social abilities. This can be seen from the average value of children's social abilities before and after being treated is from 6.4 to 13.867. This is also evidenced from the results of hypothesis testing where Tcount> T table, namely 5.797> 1.701